2010
DOI: 10.1007/s11164-010-0199-1
|View full text |Cite
|
Sign up to set email alerts
|

Direct synthesis of hydrogen peroxide from hydrogen and oxygen over insoluble Pd0.15M2.5H0.2PW12O40 (M = K, Rb, and Cs) heteropolyacid catalysts

Abstract: Palladium-containing insoluble heteropolyacid (HPA) catalysts (Pd 0.15 M 2.5 H 0.2 PW 12 O 40 ) were prepared by an ion-exchange method using various alkaline metal ions (M = K ? , Rb ? , and Cs ? ) (denoted as Pd-KPW, Pd-RbPW, and Pd-CsPW). They were then applied to the direct synthesis of hydrogen peroxide from hydrogen and oxygen. Conversion of hydrogen over the catalysts was almost identical with no great difference, while selectivity for hydrogen peroxide increased in the order of Pd-KPW \ Pd-RbPW \ Pd-Cs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Similar results were observed by Park et al in Pd exchanged heteropolyacid catalysts using various alkaline metal ions [109]. It was found that the catalyst incorporating Cs showed the highest rates of conversion and overall H 2 O 2 yield with respect to those incorporating K and Rb.…”
Section: Effect Of the Aciditysupporting
confidence: 87%
See 1 more Smart Citation
“…Similar results were observed by Park et al in Pd exchanged heteropolyacid catalysts using various alkaline metal ions [109]. It was found that the catalyst incorporating Cs showed the highest rates of conversion and overall H 2 O 2 yield with respect to those incorporating K and Rb.…”
Section: Effect Of the Aciditysupporting
confidence: 87%
“…This, however, implies some corrosion problems, especially in view of possible applications on a large scale, and the use of these additives should be avoided as much as possible. This is why a large variety of acidic supports have been tested in H 2 O 2 synthesis, especially in recent years [104][105][106][107][108][109][110].…”
Section: Effect Of the Aciditymentioning
confidence: 99%
“…Due to their high acidity numerous studies have investigated heteropolyacids as both catalyst supports,, as well as solid acid additives for the direct synthesis of H 2 O 2 . Problems concerning their low surface area and high solubility in polar solvents can be overcome through the introduction of specific cations, such as Cs + , K + and Rb + into the structure of the heteropolyacid, while other studies have investigated palladium exchanged heteropolyacids immobilized onto mesoporous silica for the synthesis of H 2 O 2 ,.…”
Section: Choice Of Support For Precious Metal Catalystsmentioning
confidence: 99%
“…The nature of the support is a key factor which can affect catalytic activity and selectivity towards H 2 O 2 . A range of zeolitic, oxide, resin,,, , heteropolyacid, and carbon,,, supports have been investigated to date.…”
Section: Choice Of Support For Precious Metal Catalystsmentioning
confidence: 99%
“…Choudhary and co-workers [12][13][14][15][16][17][18][19][20][21] use an acidic aqueous medium (sulfuric or phosphoric acid), in most cases with one or more halide promoter. Park and co-workers [22][23][24][25][26][27][28][29][30][31][32] use a solution of methanol with dissolved NaBr. Biasi and co-workers [33][34][35][36][37][38][39] generally use methanol in the absence of promoters, but have also used acidified, bromidepromoted aqueous solutions [40].…”
Section: Introductionmentioning
confidence: 99%